Charlie Chaplin's The great dictator - Willson, Meredith 1902-1984 (<<The>> Criterion Coll., 2011)
In Chaplin's first talkie, he plays the duel role of dictator Adenoid Hynkel and a Jewish barber who is a dead-ringer look-alike for der Nutsie...and who thwarts his plans for world domination
Bildformat 1.33:1. - New, restored high-definition digital transfer
Orig.: USA, 1940
Enth. new audio commentary by Charlie Chaplin historians Dan Kamin and Hooman Mehran ; "The tramp and the dictator" (2001), Kevin Brownlow and Michael Kloft's documentary paralleling the lives of Chaplin and Hitler, including interviews with author Ray Bradbury, director Sidney Lumet, screenwriter Budd Schulberg and others ; two new visual essays, one by Chaplin archivist Cecilia Cenciarelli and one by Chaplin biographer Jeffrey Vance ; color production footage shot by Chaplin's half-brother Sydney ; barbershop sequence from Sydney Chaplin's 1921 film "King, queen, joker" ; deleted barbershop sequence from Chaplin's 1919 film "Sunnyside"